Effect of the breed on selected physical and chemical quality characteristics of lamb meat - Kuchtík, Jan; Dračková, Eliška; Komprda, Tomáš; Filipčík, Radek (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2019)
The main aim of the present study was to evaluate the effect of the breed on selected physical and chemical quality characteristics of lamb meat. An integral part of the study was an assessment of growth and basic carcass traits. Three breeds (Zwartbles (ZW), Suffolk (SF) and Oxford Down (OD) of lambs were used in the experiment, which were slaughtered at the preferred liveweight (around 38 kg). The experiment was carried out at an organic sheep farm in the northern Moravia region of the Czech Republic. The genotype had a significant effect on weights of kidney and kidney fat. The genotype had also significant effect on both conformation score (CS) and fatness score (FS). With regard to physical and chemical quality characteristics of lamb meat, the genotype had a significant effect on contents of dry matter (DM), ash, collagen, myoglobin and intramuscular fat (IMF). On the other had the genotype hand no significant effect on pH24, water-holding capacity, lightness index (LI), redness index (RI) and yellowness index (YI). The genotype also had no significant effect on average daily gain (ADG) and dressing percentage (DP). In general, it can be stated that the highest ADG (170 g) and the best CS (3.8) and FS (2.2) were found in SF. However in ZW, which is dual-purpose breed compared to SF and OD, relatively high DP (49.2 %), low FS (2.2), relatively high contents of ash (1.12 %) and protein (19.00 %) and low content of IMF (1.74 %) were found. In these lambs were also found comparable values of LI, RI and YI with other meat breeds.